Pembuatan Media Promosi Berupa E-Katalog pada PT PLN (Persero) UPDL Pandaan - Della Putri Zalianti; Fatkhur Rochman (Jurnal Ilmu Sosial dan Humaniora, 2026)
Digital technology developments encourage companies to utilize effective promotional media to convey information to consumers. PLN Unit Pelaksana Pendidikan dan Pelatihan (UPDL) Pandaan has supporting facilities for internal and external parties. However, facility promotion is still limited to word-of-mouth communication and lacks an e-catalog capable of presenting information clearly, structurally, and accessibly. This condition causes facility information to be delivered sub optimally to prospective users. This research aims to create an e-catalog and determine its effectiveness as a promotional medium at PLN UPDL Pandaan. The study focuses on developing a Flipbook-based e-catalog using an Action Research approach encompassing planning, action, observation, and reflection. The research was conducted in two cycles to perfect the e-catalog results. Data collection used observation and questionnaires involving thirty respondents: marketing experts, design experts, internal staff, and prospective service users. Data were analysed using the EPIC Rate method to measure promotional media effectiveness. Analysis results show effectiveness increased from score 4.43 in the first cycle to 4.62 in the second cycle. This improvement proves the second cycle enhancements perfected both content and appearance. The e-catalog was successfully created as highly effective, making it suitable for implementation and regular updates as digital promotional media for PLN UPDL Pandaan.